294. Spondylodiscitis After Spine Surgery: Microbiology, Clinical Findings, Outcome and Comparison With Spontaneous Spondylodiscitis. (26th November 2018) - Kim, Uh Jin; Jung, Younggon; Oh, Tae Hoon; Bae, Ji Yun; Kim, Seong Eun; Kim, Chung-Jong; Kang, Seung-Ji; Jang, Hee-Chang; Jung, Sook-In; Song, Kyoung-Ho; Kim, Eu Suk; Kim, Hong Bin; et al.
Abstract: Background: Although postoperative spondylodiscitis has become a major problem, consensus on empirical antibiotics therapy is still controversial. To find out appropriate management of postoperative spondyodiscitis, this study investigated the microbiology, clinical characteristics, and outcome of postoperative pyogenic spondylodiscitis (P-PS) and compared with spontaneous pyogenic spondylodiscitis (S-PS). Methods: This retrospective cohort study evaluated patients with microbiologically proven spondylodiscitis from three university-affiliated hospitals in South Korea between January 2005 and December 2015, with a follow-up of at least 12 months after completion of antibiotics or until the patient was transferred. Patients with prosthesis at the time of diagnosis of spondylodiscitis or who had a spine operation within 1 year of the diagnosis of spondylodiscitis were defined as having postoperative spondylodiscitis. The spine operations included discectomy, laminectomy, arthrodesis, and instrumentation for stabilization of the spine. Results: The study evaluated 104 patients with P-PS and 441 patients with S-PS. In P-PS, the most common isolate was S . aureus (34%), followed by coagulase-negative staphylococci (31%), and the proportion of methicillin-resistant strains was 75%. In S-PS, the most common isolates were S . aureus (47%) and streptococci (21%). Of the staphylococci, 39% were methicillin resistant in S-PS. The proportion of patients with Gram-negative bacilli was 14% in P-PS and 20% in S-PS. Pre-existing or synchronous nonspinal infection (13% vs. 33%, P < 0.001) was observed more frequently in S-PS. Although the duration of antibiotic use was similar in both groups, surgical procedures were done more frequently in P-PS. The mortality rate was similar in both groups. However, the treatment failure and relapse rates at 12 months were higher in the P-PS group (23% vs. 13%, P = 0.009; 14% vs. 7%, P = 0.028, respectively). Methicillin-resistant S . aureus was associated with treatment failure or relapse. Conclusion: Gram-positive organisms, mainly methicillin-resistant staphylococci, should be considered when prescribing empirical antibiotics in P-PS. Although surgical drainage was applied more often in P-PS than in S-PS, the treatment failure and relapse rates at the 12-month follow-up were higher in P-PS. Disclosures: All authors: No reported disclosures.